World Health Organization Surgical Safety Checklist: Compliance and Associated Surgical Outcomes in Uganda’s Referral Hospitals - Igaga, Elizabeth N.; Sendagire, Cornelius; Kizito, Samuel; Obua, Daniel; Kwizera, Arthur (Anesthesia & Analgesia, 2018)
A pilot study on the World Health Organization (WHO) Surgical Safety Checklist (SSC) showed a reduction in both major complications and mortality of surgical patients. Compliance with this checklist varies around the world. We aimed to determine the extent of compliance with the WHO SSC and its association with surgical outcomes in 5 of Uganda’s referral hospitals. METHODS: A multicentre prospective cohort study was conducted in 5 referral hospitals in Uganda. Using a questionnaire based on the WHO SSC, patients undergoing surgical operations were systematically recruited into the study from April 2016 to July 2016. The patients were followed up daily for 30 days or until discharge for the purpose of documentation of complications. Logistic regression and linear regression were used to assess for association between compliance and perioperative surgical outcomes. RESULTS: We recruited 859 patients into the study. Overall compliance with the WHO SSC was 41.7% (95% confidence interval [CI], 39.7–43.8) ranging from 11.9% to 89.8% across the different hospitals. Overall compliance with “sign in” was 44.7% (95% CI, 43–45.6), with “time out” was 42.0% (95% CI, 39.4–44.6), and with “sign out” was 33.3% (95% CI, 30.7–35.9). There was no association between compliance and perioperative surgical outcomes: length of hospital stay, adverse events, and mortality. CONCLUSIONS: This study revealed low levels of compliance with the WHO SSC. There was a statistically significant association between this level of compliance and the incidence of pain and loss of consciousness postoperatively.
Keywords: Surgical Safety; Surgical Outcomes; Uganda’s Referral Hospitals